Simply lean simulations: bridging dynamic discrete-event simulation and Lean Six-Sigma process improvement techniques - Vlachogiannis, Eugene (Cranfield University, 2005)
Techniques part of the Lean manufacturing philosophy have been widely adopted as a method of improving flow, while at the same time reducing waste within most type of business processes. The financially driven approach of the Six Sigma has not always combined easily with the flow-based principles within lean manufacturing philosophy, but the combination of these two techniques has been proven in the past to be possible with the evolution of the Lean Six Sigma philosophy. That approach can actually improve value to the customer as well as reduce the variation and waste within the critical processes of an organisation in order to deliver real financial benefits to the supply chain. In the past lean practitioners have been wary to whatever had to do with the computer based simulations both due to the time that is needed to be spent in finalising the current and the future state maps and also due to the fact that lean practitioners seem to favour a more hands-on communication with the process itself, rather than a remote analysis like the simulation. Recognition of the “static” drag and drop value stream mapping software, gives an indication that lean practitioners are beginning to accept more the computer-based solutions in order to support collaboration and communication of value stream mapping. BRM3 Ltd, the sponsoring company for this project, have developed a discovery learning simulation exercise called "Simply Lean", which is designed to take its participants from a basic to a full understanding of how to apply the most complex techniques which underpin Lean Six Sigma. The purpose of the project is to investigate the extent to which a library of Lean Templates can be built in Simprocess, so that the enhancement of the learning experience as well as to demonstrate the validity of the simulation as a lean process improvement tool. The investigation in this project is covering the following tasks; Firstly, the successful build of simulation models in Simprocess for each of the two key stages of the simulation exercise. The first model will replicate the Push processing technique used by many small companies the second a Mixed Pull system. Both the models were built with more successful to be the Push model, and the Mixed Pull to be partially incomplete. Secondly, the creation of a “Template Library” consisting of drag and drop V.S.M Icons in Simprocess, in order that simulations models can mimic the accepted appearance of a value stream maps. This was done in full very successfully and in conjunction with the previously mentioned simulation models, the third and last objective was achieved which is the evaluation of the effectiveness of Simprocess within a “Simply Lean” workshop, which was proved as successful since both the models are able to be used as training tools as well as an implementation aid within lean six sigma projects.